Hybrid Broussonetia papyrifera Fermented Feed Can Play a Role Through Flavonoid Extracts to Increase Milk Production and Milk Fatty Acid Synthesis in Dairy Goats - Zhao, Mengjie; Lv, Dongliang; Hu, Jingcao; He, Yonglong; Wang, Zhi; Liu, Xinyu; Ran, Benkang; Hu, Jianhong (Frontiers in Veterinary Science, 2022)
In order to explore the effect of paper mulberry fermented feed on milk production and milk quality of dairy goats, and to compare with alfalfa hay, three dairy goat diets were designed based on the principle of equal energy and equal protein. The goats in the control group were fed a basic TMR diet (CG group), and the other two groups were supplemented with 10% alfalfa hay (AH group) and 10% paper mulberry fermented feed (PM group). The results showed that the dry matter intake and milk production of PM goats increased significantly. The total amount of amino acids and the content of each amino acid in the milk of AH goats and PM goats were lower than those of CG goats. The content of saturated fatty acids (C17:0) in the milk of PM group decreased while the content of unsaturated fatty acids (C18:3n-3, EPA and DHA) increased. The contents of prolactin, estrogen and progesterone in PM goat serum are generally higher than those of AH goat and CG goat. Subsequently, this study separated and cultured mammary epithelial cells from breast tissue, and added flavone extracted from paper mulberry and alfalfa to their culture medium for comparison, which is one of their important bioactive components. The results showed that low-dose alfalfa flavone (AH) and paper mulberry flavone (PM) can increase cell viability. They also can increase the accumulation of intracellular triglyceride and the formation of lipid droplets. Both AH flavone and PM flavone significantly up-regulated the expression of genes related to milk fat synthesis, including genes related to fatty acid de novo synthesis (ACACA, FASN, SCD1), long-chain fatty acid activation and transport related genes (ACSL1), and genes related to transcription regulation (SREBP1). The mRNA content of PPARA and PPARG was significantly increased by PM flavone, and AH flavone significantly increased the expression of PPARG gene. The three genes related to triglyceride synthesis (DGAT1, DGAT2, GPAM) were all significantly increased by paper mulberry flavone. Both AH flavone and PM flavone significantly increased the expression of progesterone receptor and estrogen receptor in mammary epithelial cells but had no effect on prolactin receptor.